2017
DOI: 10.1038/ncomms15338
|View full text |Cite
|
Sign up to set email alerts
|

Notch-mediated conversion of activated T cells into stem cell memory-like T cells for adoptive immunotherapy

Abstract: Adoptive T-cell immunotherapy is a promising approach to cancer therapy. Stem cell memory T (TSCM) cells have been proposed as a class of long-lived and highly proliferative memory T cells. CD8+ TSCM cells can be generated in vitro from naive CD8+ T cells via Wnt signalling; however, methods do not yet exist for inducing TSCM cells from activated or memory T cells. Here, we show a strategy for generating TSCM-like cells in vitro (iTSCM cells) from activated CD4+ and CD8+ T cells in mice and humans by coculturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 39 publications
1
88
0
Order By: Relevance
“…Stem cell memory T cells expressed naïve T‐cell surface markers, CD44 low CD62L high CCR7 + in mice and CD45RA + CD45RO − CCR7 + CD62L + in humans . These cells possess high proliferative and long‐term survival abilities in vivo, producing a large number of effector T cells with potent antitumor functions . Similar naïve‐like memory T cells were discovered in human and called memory T cells with a naive phenotype .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Stem cell memory T cells expressed naïve T‐cell surface markers, CD44 low CD62L high CCR7 + in mice and CD45RA + CD45RO − CCR7 + CD62L + in humans . These cells possess high proliferative and long‐term survival abilities in vivo, producing a large number of effector T cells with potent antitumor functions . Similar naïve‐like memory T cells were discovered in human and called memory T cells with a naive phenotype .…”
Section: Introductionmentioning
confidence: 89%
“…[16][17][18][19][20] We have established a novel two-step culture system for T SCM induction, which is constituted by a "prime" step and an "induction" step, and have named the induced-T SCM "induced-T SCM (iT SCM )" cells. 12 In this paper, we describe a detailed methodology of iT SCM generation and report optimal conditions of priming and cytokine treatment. We also investigate the antitumor efficacy of human iT SCM cells in a humanized mouse model.…”
Section: Memory T Cells Have Been Classified Into Two Subpopulationsmentioning
confidence: 99%
“…The number of memory T cells required for initial adoptive transfer therapy will be significantly lower than the current practice as memory cells can be primed in vivo using vaccine to regenerate CTL as needed. Current approaches to induce Tscm-like ACT include 1) Cytokines addition: IL-7, IL-15, IL-21 [70]; 2) using inhibitors for AKT,m-TORC and PI3K [71,72]; 3) activation of NOTCH [73]; 4) Weak TCR signaling during activation [74]; 5)providing additional costimulation e.g. 4-1BB, ICOS [75]; 6) altered metabolism status [76,77].…”
Section: The Influence Of Immunosuppressive Tumor Microenvironment (Tmentioning
confidence: 99%
“…A recent study indicated that Notch signaling redirects differentiation from memory precursor-like activated CD8 + T cells to stem cell memory T-like cells, which have a long-lived and self-renewing potential [75]. Interestingly, miRNAs, such as miR-34, miR-598 and miR-433, regulate cancer stem cells by targeting the molecules of the Notch signaling pathway [76][77][78].…”
Section: Mirna Regulation Of Signaling Pathwaysmentioning
confidence: 99%